2010
DOI: 10.1016/j.jml.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

On the incrementality of pragmatic processing: An ERP investigation of informativeness and pragmatic abilities

Abstract: In two event-related potential (ERP) experiments, we determined to what extent Grice’s maxim of informativeness as well as pragmatic ability contributes to the incremental build-up of sentence meaning, by examining the impact of underinformative versus informative scalar statements (e.g. “Some people have lungs/pets, and…”) on the N400 event-related potential (ERP), an electrophysiological index of semantic processing. In Experiment 1, only pragmatically skilled participants (as indexed by the Autism Quotient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 106 publications
(183 reference statements)
13
168
1
Order By: Relevance
“…These early disruptions as indexed by first-pass reading times and, crucially, the N400, were taken as evidence that mapping utterances onto pre-existing world knowledge is an inevitable consequence of the memory retrieval mechanisms by which we compute meaning, and that counterfactual context comes into play at a later moment ; but see Ferguson, Sanford, & Leuthold, 2007, who reported N400 evidence for rapid integration into an affirmative, rather than negated counterfactual world). These conclusions resonate with the long-held assumption that non-propositional semantic processes precede post-semantic decision processes that compute sentence truth-value, based on the insensitivity of the N400 to propositional truth-value in sentences containing logical operators (e.g., Fischler et al, 1983;Kounios & Holcomb, 1992;Urbach & Kutas, 2010; but see Nieuwland, Ditman, & Kuperberg, 2010;Nieuwland & Kuperberg, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…These early disruptions as indexed by first-pass reading times and, crucially, the N400, were taken as evidence that mapping utterances onto pre-existing world knowledge is an inevitable consequence of the memory retrieval mechanisms by which we compute meaning, and that counterfactual context comes into play at a later moment ; but see Ferguson, Sanford, & Leuthold, 2007, who reported N400 evidence for rapid integration into an affirmative, rather than negated counterfactual world). These conclusions resonate with the long-held assumption that non-propositional semantic processes precede post-semantic decision processes that compute sentence truth-value, based on the insensitivity of the N400 to propositional truth-value in sentences containing logical operators (e.g., Fischler et al, 1983;Kounios & Holcomb, 1992;Urbach & Kutas, 2010; but see Nieuwland, Ditman, & Kuperberg, 2010;Nieuwland & Kuperberg, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…We assume it is probably the case that common features underlie these two cognitive abilities. In the adult psycholinguistic literature, it has been found that individuals with lower self-reported pragmatic abilities had a lower standard of relevance, to the extent that they were less likely to draw pragmatic inferences based on linguistic stimuli (Nieuwland et al, 2010) and were less likely to do well on the communication subset of the ASQ questionnaire (Baron-Cohen et al, 2001). Further studies are needed to determine whether individual differences in terms of social competence are linked with performance in such referential tasks and, in the case of too much information, what makes them go as far as trying to explain the infelicity by looking for a contrast object.…”
Section: Discussionmentioning
confidence: 99%
“…These results beg the question why a thematic conflict plays out in the N400 component. N400 modulations are thought to index wordelicited retrieval from semantic memory, facilitated by contextually-guided predictions (for review, see Kutas et al, 2006), and modulated by relevance signals such as focus (e.g., Nieuwland, Ditman, & Kuperberg, 2010;Schumacher & Baumann, 2010). Why does missing case-marking elicit an N400 effect?…”
Section: Asymmetric N400 Modulations For Case Violationsmentioning
confidence: 99%